Power Restricted Realties: A Post-structuralist Critique of The Matrix - Aswin Prasanth Rose Mary Jose (Singularities : A Transdisciplinary Biannual Research Journal, 2016)
The Matrix is a 1999 cyber punk science fiction film written and directed by The Wachowskis. It is set in a dystopian future where reality as perceived by humans is a simulated reality called “The Matrix.” This simulated reality was created by sentient machines to control the entire human race. Neo, the protagonist, finds the truth and joins a group of people, who have escaped from the simulated reality, to fight against the domination of the machines and to free every human from “The Matrix.” The film incorporates themes from Jean Baudrillard's Simulacra and Simulation and Michel Foucault's Discipline and Punish: The Birth of the Prison. The character Agent Smith, created by the machines to prevent humans from escaping “The Matrix,” exerts constant surveillance on everyone inside the simulated reality. This can be seen as the concept of panoptic surveillance laid out by Foucault where oppressive power structures constantly keep watch of subordinate or marginalized groups. The simulated reality, “The Matrix,” is based on Baudrillard's concept of hyperreality wherein an image has no connection to reality. The film shows how power constructs and controls reality and how man becomes a victim of power and is circumscribed by notions of reality. This paper is a post-structuralist critique of The Matrix undertaken from the interconnectedness of power and reality as conceived by Foucault and Baudrillard.